Endodontic flare ups: A proposal for etiopathogenesis and psychological management - Kaur, Pushappreet (International Journal of Health, 2015)
Flare ups are undesirable yet unavoidable, true endodontic emergencies, presenting with severe pain and/or swelling of the facial soft tissues and the oral mucosa in the area of endodontically treated tooth, in association with strong expression of clinical symptoms (tooth pain when biting, chewing or by itself), occuring within a few hours or a few days of instrumentation. Prevention and management of such situations necessitates standardized execution of all the steps comprising root canal therapy alongwith comprehensive knowledge of its possible etiological factors, pathogenesis, pharmacological and non-pharmacological treatment methods. This article presents a pro-posal for etiopathogenesis and psychological management besides accounting a brief description of its definition, epidemiology, treatment steps and prevention.